Lnc-C2orf63-4-1 Confers VSMC Homeostasis and Prevents Aortic Dissection Formation via STAT3 Interaction - Zhang, Song; Zhao, Shiqi; Han, Xuejie; Zhang, Yun; Jin, Xuexin; Yuan, Yue; Zhao, Xinbo; Luo, Yingchun; Zhou, Yun; Gao, Yunlong; Yu, Hui; Sun, Danghui; et al. (Frontiers in Cell and Developmental Biology, 2021)
Emerging evidence indicates that long non-coding RNAs (lncRNAs) serve as a critical molecular regulator in various cardiovascular diseases. Here, we aimed to identify and functionally characterize lncRNAs as potential mediators in the development of thoracic aortic dissection (TAD). We identified that a novel lncRNA, lnc-C2orf63-4-1, was lowly expressed in aortic samples of TAD patients and angiotensin II (Ang II)-challenged vascular smooth muscle cells (VSMCs), which was correlated with clinically aortic expansion. Besides, overexpression of lnc-C2orf63-4-1 significantly attenuated Ang II-induced apoptosis, phenotypic switching of VSMCs, and degradation of extracellular matrix both in vitro and in vivo. A customized transcription factor array identified that signal transducer and activator of transcription 3 (STAT3) functioned as the main downstream effector. Mechanistically, dual-luciferase report analysis and RNA antisense purification (RAP) assay indicated that lnc-C2orf63-4-1 directly decreased the expression of STAT3, which was depend on the reduced stabilization of STAT3 mRNA. Importantly, up-regulation of STAT3 efficiently reversed the protective role of lnc-C2orf63-4-1 against Ang II-mediated vascular remodeling. Therefore, lnc-C2orf63-4-1 negatively regulated the expression of STAT3 and prevented the development of aortic dissection. Our study revealed that lnc-C2orf63-4-1 played a critical role in vascular homeostasis, and its dysfunction exacerbated Ang II-induced pathological vascular remodeling.